The star fisher - Yep, Laurence, 1948- (New York Scholastic, 1991)
Fifteen-year-old Joan Lee and her family find the adjustment hard when they move from Ohio to West Virginia in the 1920's.
S
b
b
Keywords: Chinese Americans -- Juvenile fiction; Prejudices -- Juvenile fiction